2013
DOI: 10.14693/jdi.v19i1.123
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Force Application in Correlation with Salivary Lactate Dehydrogenase Activity

Abstract: Orthodontic tooth movement generate mechanical forces to periodontal ligament and alveolar bone. The forces correlate with initial responses of periodontal tissues and involving many metabolic changes. One of the metabolic changes detected in saliva is lactate dehydrogenase (LDH) activity. Objectives: To evaluate the correlation between orthodontic interrupted force application, lactate dehydrogenase activity and the distance of tooth movement. Methods: upper premolar, pre-retraction of upper canine and 1, 7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…Values were significantly higher after 3 months compared to after 1month, meaning that there was a progressive rise with increased treatment duration. The present study was in line with that of Husin et al 22 who reported that orthodontic interrupted force application caused an increase in the salivary LDH. The increase in LDH activity in the saliva of our patients during removable appliances treatment may be explained by having increased retention sites for microbial samples compared to before treatment which may be responsible for gingivitis.…”
Section: Discussionsupporting
confidence: 93%
“…Values were significantly higher after 3 months compared to after 1month, meaning that there was a progressive rise with increased treatment duration. The present study was in line with that of Husin et al 22 who reported that orthodontic interrupted force application caused an increase in the salivary LDH. The increase in LDH activity in the saliva of our patients during removable appliances treatment may be explained by having increased retention sites for microbial samples compared to before treatment which may be responsible for gingivitis.…”
Section: Discussionsupporting
confidence: 93%
“…Adhitya et al 23 reported an increase in ASAT. Similarly, Husin et al 24 found a significant increase in LDH levels that was correlated with dental movements and the duration of orthodontic forces. To the contrary, Totan et al 25 found no significant changes in ALAT rates even when associated with periodontal disease.…”
Section: Discussionmentioning
confidence: 79%
“…Proses remodeling tulang yaitu penurunan jumlah ligament periodontal dan tulang alveolar pada sisi resorpsi oleh osteoklas dan pada daerah aposisi mengalami remodeling dan terjadi pembentukan tulang baru oleh osteoblas, peristiwa ini terjadi secara bergantian 4 . Pada hari ke 3-5 dimana terjadi awal resorpsi, lalu diikuti fase penyembuhan pada hari ke 5-7, dan pada hari 7-14 tahap ahkir resorpsi tulang 27 .…”
Section: Pembahasanunclassified